Predictors of obesity hypoventilation syndrome among patients with sleep-disordered breathing in India - Mahismita Patro; Dipti Gothi; Umesh Chandra Ojha; Sameer Vaidya; Ram Babu Sah (Lung India, 2019)
Introduction: No study has been done in India to evaluate obesity hypoventilation syndrome (OHS) among patients with sleep-disordered breathing (SDB). The known predictors of OHS, i.e., body mass index (BMI) >35 kg/m2 and forced vital capacity (FVC) <3.5 L for men and <2.3 L for women from western countries, cannot be applied to Indian patients. Objectives: To find out the prevalence of OHS and to determine the predictors of OHS among Indian SDB patients. Materials and Methods: It was a retrospective observational study conducted in a tertiary care institute from September 1, 2017, to August 31, 2018. All the patients who underwent polysomnography were analyzed for the presence of OHS. Of 85 patients referred for polysomnography, 76 had SDB. Thirteen patients were excluded because of hypoventilation due to other known causes or could not perform spirometry. Results: The prevalence of OHS among SDB after excluding the other causes of hypoventilation was 15.87% (10/63). The predictors were determined using univariate analysis between daytime partial pressure of carbon dioxide (PaCO2) and other predictors. PaCO2 significantly correlated with minimum nocturnal oxygen saturation by pulse oximetry (SpO2), FVC %predicted, BMI, daytime SpO2, forced expiratory volume %predicted, and partial pressure of oxygen (PaO2). Following a stepwise multiple regression, minimum nocturnal SpO2, FVC %predicted, and BMI were found to be independent predictors of OHS. A minimum nocturnal SpO2 threshold of 60%, FVC %predicted <74.5%, BMI >30.95 kg/m2, and absolute FVC <2.33 L for men and <1.68 L for women were found to be predictors of OHS. Conclusion: The prevalence of OHS in Indian patients is similar to Caucasians. OHS is seen in Indian patients even at a lower BMI and lower spirometric parameters.